A novel controller for PV-fed water pumping optimization system driven by an 8/6 pole SRM with asymmetrical converter - Kumar Kolluru, Ashok; Malligunta, Kiran Kumar; Teja, S. Ravi; Reddy, Ch. Rami; Alqahtani, Mohammed; Khalid, Muhammad (Frontiers in Energy Research, 2023)
Locally installed photovoltaic (PV) powered motor pump is the feasible solution for water pumping system (WPS) in rural locations. A single stage PV-fed SRM powered WPS is investigated and realized using speed sensor less sliding mode controller (SMC) based direct torque controller (DTC) in this study. As a result, no additional DC-DC converter is required for maximum power absorption from PV source. By utilizing a novel high side switch asymmetric converter with hybrid Perturb and Observe – Grey Wolf optimization (POGWO) method integrated to with dc-link voltage controller, an efficient single stage conversion is achieved. The robustness of the proposed integrated control is presented by comparing it with the genetic algorithm and particle swarm optimization (PSO). Extensive results using MATLAB SIMULINK are shown to validate the proposed system in both steady state and transient conditions for various partial shaded conditions.